Geography : - Boehm, Ricchard G. (Glencoe/McGraw-Hill, 1998)
Geography: The World and Its People is the only program specifically developed for inquiring middle school students and co-authored by the National Geographic Society. It brings the world to your classroom with bold graphics, hands-on activities, a variety of themes, and the vivid, in-depth research and resources for which the National Geographic Society is known.